Ferula gummosa gum induces apoptosis via ROS mechanism in human leukemic cells - Moradzadeh, Maliheh; Sadeghnia, Hamid Reza; Mousavi, Seyed Hadi; Mahmoodi, Merat; Hosseini, Azar (Cellular and Molecular Biology, 2017)
Ferula species known for its oleo-resins that are recognized valuable industrial crops and food products. In this study, we examined the level of cellular oxidants, cytotoxicity, apoptosis and differentiation induced by oleo resin gum from Ferula gummosa (30-250 µg/mL), as well as Arsenic trioxide (50 µM, as positive control), in leukemic (NB4 and HL-60 cells) and normal polymorph nuclear cells during 72 h. Resazurin assay was used to determine cell viability following treatment with F. gummosa (30-250 µg/mL). Intracellular reactive oxygen species was measured by fluorimetry using carboxy 2"², 7"²-dichlorofluorescein diacetate. Apoptotic cells were evaluated using PI staining of DNA fragmentation by flow cytometry (sub-G1 peak). Differentiation of cells evaluated by Giemsa staining and Nitro Blue Tetrazolium reduction. F. gummosa showed a concentration-dependent suppression in cell survival with IC50 values of 41.8 µg/mL for HL60 and 59.2 µg/mL for NB4 cells after 72 h treatment. ROS formation and apoptotic cells were concentration-dependently increased following treatment with F. gummosa, similar to As2O3. F. gummosa did not induce differentiation of leukemic cells towards granulocytic pattern. The resin did not have toxic effect on PMN cells (<800 µg/mL). In conclusion, the present study demonstrated that F. gummosa induced apoptosis through ROS mechanism on leukemic cells as a concentration and time dependent manner. The precise signaling pathway by which F. gummosa induce apoptosis needs further research.